Spontaneous Coronary Artery Dissection in a Male Patient with Takayasu’s Arteritis and Antiphospholipid Antibody Syndrome - Demet Menekşe Gerede; Bağdagül Yüksel; Eralp Tutar; Orhan Küçükşahin; Çağlar Uzun; Kayhan Çetin Atasoy; Nurşen Düzgün; Uğur Bengisun (Case Reports in Rheumatology)
We present a case of a 34-year-old male who presented to the emergency ward with fever and abdominal pain. The diagnosis of Takayasu’s arteritis and also antiphospholipid syndrome was made during an imaging workup of deep-vein thrombosis. A spontaneous coronary artery dissection was revealed in coronary CT angiography requested for chest pain and dyspnea. The patient was treated medically and discharged on close followup. The concurrence of spontaneous coronary artery dissection with antiphospholipid syndrome and Takayasu’s arteritis has not been reported in the previous literature. The possibility of a spontaneous coronary artery dissection should be considered in patients presenting with both diseases.